Respuesta :

17x - 9(x + 4) = 3x - 26

First, expand to remove parentheses.
[tex]17x - 9x - 36 = 3x - 26[/tex]
Second, subtract 17x - 9x to get 8x.
[tex]8x - 36 = 3x - 26[/tex]
Third, add 36 to both sides. 
[tex]8x = 3x - 26 + 36[/tex]
Fourth, simplify.
[tex]8x = 3x + 10[/tex]
Fifth, subtract 3x from both sides.
[tex]8x - 3x = 10[/tex]
Sixth, subtract 8x - 3x.
[tex]5x = 10[/tex]
Seventh, divide both sides by 5.
[tex]x = \frac{10}{5} [/tex]
Eighth, since 2 goes into 5 to get 10, simplify the fraction to 2.
[tex]x = 2[/tex]

Answer: x = 2